Mechanism of nanotubular Ta2O5 via anodization in NH4F/H2SO4/H2O solution / Mahzaton Aqma Abu Talip ...[et al.] - Abu Talip, Mahzaton Aqma; Abdul Rani, Rozina; Ab Kadir, Rosmalini; Mamat, Mohamad Hafiz; Abdul Khalid, Muhammad Farid; Mahmood, Mohamad Rusop; Zoolfakar, Ahmad Sabirin (UiTM Press, 2018)
The main subject of many studies in anodization of Ta2O5 is to investigate the role of electrolyte composition on nanostructure Ta2O5 formation. However, the simple and clear explanation on how electrolyte composition affects the mechanism of nanotubular formation is hardly to be found. In this paper, we provided organized and step by step discussion on how NH4F, H2O and H2SO4 influence the growth of nanotubular by performing the experiments with different concentration of NH4F, H2O and H2SO4. The electrochemical formation of nanotubular tantalum pentoxide (Ta2O5) was investigated in 50 ml ethylene glycol (EG), 0.5-3 wt% of NH4F, 0-6 vol% of H2O and 0-1 vol% of H2SO4. Depending on electrolyte concentration, Ta2O5 films exhibit different structural structures and features after anodization. The results were shown through FESEM, real images of samples and XRD analysis. By varying the concentration, it was possible to change the structures of Ta2O5. Finally, we demonstrated how electrochemical response during anodization, thus forming nanotubular Ta2O5.